The Influence of Mounting Angle on Gurney Flap on The Aerodynamics Performance of NACA 0015 Using CFD Method - Lukiano, Mirza Fauzan; Julian, James; Wahyuni, Fitri; Iskandar, Waridho (International Journal of Marine Engineering Innovation and Research, 2025)
Improving the airfoil aerodynamics is quite an essential aspect of the aviation industry. One method for improving airfoil aerodynamics involves applying passive flow control techniques. The effect of using the gurney flap as passive flow control was explored through the CFD approach with the RANS control equation and incorporating k-epsilon as a turbulence model. The airfoil model utilized in this study was the NACA 0015 airfoil operating at a Reynolds number of 1×106. This study explored three different mounting angles of the gurney flap, namely 45°, 60°, and 90°. The outcomes show that adding the gurney flap has positive results in increasing the lift and drag of the NACA 0015. An airfoil with a mounting angle flap of 45° has an average percentage increase in Cl of 23%, followed by a mounting angle flap of 60°, which is 28%, and a percentage Cl of 45% for a mounting angle flap of 90°. Meanwhile, Gurney flaps with a mounting angle of 45° can increase Cd by an average percentage of 3%, while mounting angle flap at 60° increases the Cd percentage by 4% and 5% for a mounting angle of 90°. Moreover, fluid flow visualization with pressure and velocity contours was given at AoA 10º to determine its effect on increasing lift and drag on the NACA 0015 airfoil.